Effect of telerehabilitation on mobility in people after hip surgery: a pilot feasibility study. Issue 3 (September 2018) - Kalron, Alon; Tawil, Heba; Peleg-Shani, Sara; Vatine, Jean-Jacques
Abstract : The goal of this study was to evaluate the effects of telerehabilitation on mobility in people following hip surgery. This feasibility pilot randomized controlled trial included a sample of 40 participants, with 22 male and 18 female patients and mean age (SD) of 67.5 (7.8) years following a surgical intervention. Participants were equally divided and randomly assigned to a telerehabilitation or control intervention group (6 weeks, 3 sessions/week). Telerehabilitation was based on video clips of common rehabilitation exercises focusing on the lower limbs. The control group received an exercise booklet. Both groups participated in physical therapy sessions, twice a week. Outcome measures included the Timed Up and Go test, 2-min walk test, 10-m walk test, sit to stand test, walking speed, and mean step length. Measurements were completed at baseline, at termination of the intervention, and at a 4-week follow-up examination. Improvements in both groups were demonstrated in all outcome measures in the postintervention evaluation. Improvements in the telerehabilitation group were greater in five of six tests compared with those achieved by the controls. The telerehabilitation group showed greater improvements in the 2-min walking test (86.1%) and walking speed (65.6%). During follow-up, the telerehabilitation group continued to improve in all outcome measures in contrast to the control group, who showed no changes in five of the six outcome measures. Telerehabilitation, a complementary treatment to standard physical therapy, generates a positive effect on mobility in people following hip surgery.